Antimicrobial Effect of Acanthopanax sessiliflorum Fruit Extracts against Selected Oral Bacteria - Choi, Won-Ik; Jeong, Moon-Jin; Jung, Im-Hee; Lim, Do-Seon (Chiwisaeng gwahakoeji, 2018)
This study aimed to evaluate the antimicrobial effects of Acanthopanax sessiliflorum fruit (ASF; Ogaza) extracts on Streptococcus mutans and Streptococcus sobrinus, which are agents that cause dental caries, and on Streptococcus mitis and Streptococcus salivarius, the microbial flora of the oral cavity. The ASF extracts obtained using 70% ethanol were fractionated in the order of ethyl acetate and n-Butanol, concentrated under reduced pressure, and lyophilized to give powdery solvent extracts. The antimicrobial activity of ASF extracts from each solvent was examined using the disk diffusion method. As a result, only those extracts obtained using an ethyl acetate solvent showed antimicrobial activity. These extracts were selected, and the minimum inhibitory concentration was measured by disk diffusion method at various extract concentrations. Results showed a minimum inhibitory concentration of 32 mg/ml. The viable cell count was measured to confirm the minimum bactericidal concentration. Results showed a minimum bactericidal concentration of 64 mg/ml. In the cytotoxicity test using normal human dermal fibroblast cells, the absorbance value of the test group was similar to that of the control group at 0.64, 1.28, and 6.4 mg/ml. The bacteria and their colonies were examined using a scanning electron microscope. Boundaries between the antimicrobial activity region and non-antimicrobial activity region were observed around the paper disk, which was immersed in the extract with 32 mg/ml concentration. Bacterial colonization was not observed in the area with antimicrobial activity. This finding suggests that ASF extracts can inhibit the growth of some microorganisms in the oral cavity, in addition to the effects of these extracts known to date. In particular, ASF extracts may be used as a preparation for preventing dental caries by adding the extract to the toothpaste or oral mouthwash. KCI Citation Count: 0